The Effect of Self Efficacy, Work Experience, And Work Load On Employee Performance At PT. Centrepark Citra Corpora Branch North Sumatra - Nicholas Sitio; Henri Saragih; Jon Henri Purba; Selamat Siregar (Fakultas Ekonomi Universitas Simalungun, 2026)
This study aims to examine the extent to which Self-Efficacy, Work Experience, and Workload contribute to the improvement of employee performance at PT Centrepark Citra Corpora, North Sumatra Branch. The research method employed in this study is quantitative research. Based on the results of the partial t-test, it can be concluded that Self-Efficacy has a positive and significant effect on employee performance, with a calculated t-value of 4.943, which is greater than the t-table value of 2.096, and a significance value of 0.000 < 0.05. Work Experience also has a positive and significant partial effect on employee performance, as indicated by a calculated t-value of 14.546, which exceeds the t-table value of 2.096, and a significance value of 0.000 < 0.05. Furthermore, Workload has a positive and significant partial effect on employee performance, with a calculated t-value of 2.622, which is greater than the t-table value of 2.096, and a significance value of 0.000 < 0.05. Based on the results of the simultaneous hypothesis test (F-test), the calculated F-value is 5060.920, which is greater than the F-table value of 2.79, with a significance value of 0.000 < 0.05. Therefore, it can be concluded that Self-Efficacy, Work Experience, and Workload simultaneously have a positive and significant effect on employee performance. The results of the coefficient of determination analysis indicate that the influence of Self-Efficacy, Work Experience, and Workload on employee performance is 50.7%.